Public policy evaluation : introduction to quantitative methodolgies (Helsinki, 2020)
This paper is a survey which describes and explains in non-technical terms the logic behind various methodologies used in conducting retrospective quantitative evaluations of public policy programs. The programs usually have as their main targets firms or individuals who benefit from direct subsidies and/or training. It is hypothesised that because of the technical nature of quantitative evaluations, some of the public officials to whom these evaluations are intended, may find them too complex to comprehend fully. Hence, those officials might disregard them up front, or form a biased opinion (positive or negative) or even accept the results on their face value